Determinant of Financial Flexibility: Internal Funding, External Funding, and Moderating of Investment Firms Listed in Indonesia Stock Exchange - Sari, Pristin Prima; Hermuningsih, Sri; Hidayat, Riskin; Rahmawati, Anisya Dewi (INTERNATIONAL JOURNAL OF ECONOMICS AND MANAGEMENT REVIEW, 2024)
Purpose- The research aims to find empirical evidence of the influence of internal and external funding on financial flexibility with firms' investment moderation on the Indonesian Stock Exchange. Design/methodology/approach - The Research Method uses quantitative methods using multiple regression analysis. The sample used was the food and beverage sector on the Indonesian Stock Exchange. Data uses annual financial reports 2019-2023. Originality -  This research uses the flexibility variable as the dependent variable, whereas in most previous research, flexibility was used as the independent variable. Findings and Discussion - The research results show that internal and external funding have no significant effect on financial flexibility but investment has a significant effect on financial flexibility. Investment can moderate internal funding and external funding on financial flexibility. Conclusion - Investment can moderate internal funds and external funds to financial flexibility. Suggestion for future research to use other variable that impact on financial flexibility. This Research has recommended that firm management consider fund sources to gain financial flexibility. The Higher the financial flexibility the higher fulfill firm expenditure. The benefit of research is for managerial decision-making related to internal and external funding sources which have an impact on financial flexibility with investment moderation.